Minimally invasive primary excision and primary closure versus primary closure using mitomycin C to prevent pterygium recurrence (Annals of Medical Research, 2022)
Aim: This study aimed to present a surgical technique in which we applied minimal excision and primary closure and evaluate the recurrence rate in this technique.Materials and Methods: Data from primary pterygium excision performed from 2013 to 2019, were retrospectively analyzed from the patient's electronic database. After the pterygium detached from the cornea with the help of blunt dissection, only the cap of the pterygium was resected with a Westcott scissor by vertical incision on the vascular and avascular region border. The primary closure involved a complete closure of the defect in the limbal surface by suturing the pterygium's head. Patients who underwent only primary closure constituted Group 1, patients who underwent primary closure using mitomycin C as adjuvant therapy constituted Group 2.Results: The study comprised a total of 31 patients, including 12 participants in Group 2 and 19 in Group 1. The average age of all subjects was 58.7 ± 9.4 years. The average postoperative follow-up time of groups was 29.2 ± 20.1 months and 30.0 ± 21.9 months, respectively(p = 0.88). Recurrence was observed in 4 (12.9%) of all patients during follow-up. While recurrence occurred in 10.5% of patients in Group 1, recurrence was observed in 16.7% of patients in Group 2. When the groups were compared in terms of recurrence, no statistically significant difference was observed (p=0.62).Conclusions: This minimal excisional and maximum physiological pterygium surgery is simple, fast, and safe in primary pterygium. It also has a relatively acceptable recurrence rate.